The issue of ellipses and its effect on textual cohesion: An applied linguistic study on an Umayyad poem - Naeem, Areej Abdullah (Journal of Arabic Language Sciences and Literature, 2024)
This study investigated the occurrence of ellipsis in early and recent literature. As well as the paper seeks to conduct a traditional analysis of the text, followed by a syntactic analysis based on generative grammar, and then an analysis in line with text linguistics. The study adopted a descriptive-analytic framework for one of the Umayyad poems. In this study the applied framework consisted of two parts: First, a conventional part dealing with the criteria for the of ellipsis elements, their types, and their structural composition. Second, a statistical part that includes textual study which addresses the frequency and recurrence of ellipsis and their references throughout the entire text. The study revolved around two key questions Firstly, the role played by the ellipses in classical poetry. Secondly, the effect of the missing element's absence in the text and on its recipient. The study reached several results, the most important of which are the followingthat: : First: the Umayyad poet effectively used the technique of ellipses as a device for textual cohesion to render the desired goal, which was to express his suffering in love. Second: The textual deletions varied according to the type of speech, but the absence of the most frequent deleted element - the name of the beloved - indicates that the poem is cohesive to shed light on one topic.Third: Ellipses served multiple functions beyond facilitating textual cohesion. These included the preservation of rhyme and the poetic language, as well as fulfilling grammatical objectives. Fourthly: The grammatical analysis underscored the significance of ellipsis within the surface structure of texts, and its ability to expand the meaning when many meanings are possible, all of which are related to the context. In the end, the study concluded that integrating conventional study with textual study is indispensable within the scope of textual studies. Finally, the study recommends conducting more modern studies on heritage texts, thus reviving the ancient text by applying theories of modern linguistics.
Keywords: Ellipses; Text cohesion; Umayyad poetry; Ellipses in generative grammar; Textual Cohesion devices